On the mobilizing role of social media in revolutions: a game-theoretic approach - Hubert János Kiss; Alfonso Rosa-García (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2013)
A distinctive feature of recent revolutions was the key role of social media (e.g. Facebook, Twitter and YouTube). We study the role of social media in mobilization. In a simple model we assume that while social media allow to observe all previous decisions, mass media only give aggregate information about the state of a revolt. We show that when individuals' willingness to revolt is publicly known, then both sorts of media foster a successful revolution. However, when willingness to revolt is private information, only social media ensure that a revolt succeeds, with mass media multiple outcomes are possible. This suggests that social media enhance the likelihood that a revolution triumphs more than traditional mass media.
Keywords: C72; D02; D74; 330; social media; mass media; revolution; coordination game; sequential games